2014
DOI: 10.1177/0731684414523325
|View full text |Cite
|
Sign up to set email alerts
|

Studies on water absorption behaviour of bamboo–epoxy composite filled with cenosphere

Abstract: This paper deals with the evaluation of water absorption properties of natural fibre composites consisting of bamboo fibre as reinforcement, epoxy as matrix and cenosphere as particulate filler at different environmental conditions. Hand lay-up technique is used to fabricate the composites with varying number of layers of bamboo fibre and cenosphere filler content. Water absorption kinetics of the composites is presented in this paper. It is observed that the rate of water absorption depends on the fibre conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 33 publications
(47 reference statements)
2
19
0
Order By: Relevance
“…Therefore, higher hydrophilic nature of cellulosic fibre is the main reason of higher water sorption in bamboo-based composite and the penetration of water is mainly through the cross-sectional portion of the fibre by capillary mechanism [16]. This behaviour is in accordance with previous report [10,11] which considered various weight fractions of bamboo fibre in an epoxy matrix. In natural-fibre based composites, the free OH groups of cellulose will come in contact with water and form hydrogen bonding which results in increasing of water absorption [17,18].…”
Section: Water Sorption Behavioursupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, higher hydrophilic nature of cellulosic fibre is the main reason of higher water sorption in bamboo-based composite and the penetration of water is mainly through the cross-sectional portion of the fibre by capillary mechanism [16]. This behaviour is in accordance with previous report [10,11] which considered various weight fractions of bamboo fibre in an epoxy matrix. In natural-fibre based composites, the free OH groups of cellulose will come in contact with water and form hydrogen bonding which results in increasing of water absorption [17,18].…”
Section: Water Sorption Behavioursupporting
confidence: 90%
“…Due to its hydrophilic characteristic, the natural fibre reinforced polymer composites are mostly used for interior application [2]. The presence of water in bamboo fibre leads to weak interfacial bonding between fibres and matrix which in turn deteriorate the mechanical properties of resulted composite [10]. Based on experiments on water uptake, several studies on diffusion of water into bamboo-based polymer composites have been reported [2,5,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This happens because the density of the composite increases as the milling time is increased. Bamboo epoxy composite has 4% thickness swelling [ 40 ], which is about the same as that of the coconut shell epoxy composite from this study for 40 h duration of milling.…”
Section: Resultsmentioning
confidence: 70%
“…Water absorption test: Water absorption tests were carried out on three prismatic samples with size 64 Â 12.7 Â 3 mm 3 for each case according to ASTM D 570-98 standard, under different climatic conditions of 10 C, 30 C and 60 C. The samples were taken out from the bath at regular intervals of time, that is for every 1 h, and the water content present on the specimen surface was wiped out with a dry cloth and then weighed in a high precision digital balance. The water absorption in the weight percentage (%M) was calculated by using the following equation [32][33][34][35].…”
Section: Methodsmentioning
confidence: 99%